2023
DOI: 10.1038/s41598-023-34278-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of moderate and high-intensity interval exercises on asprosin and BDNF levels in inactive normal weight and obese individuals

Abstract: This study aimed to examine the acute effects of moderate-intensity aerobic and high-intensity interval exercise protocols on Asprosin and Brain-Derived Neurotrophic Factor (BDNF) levels in inactive normal weight and obese individuals. A total of 20 male individuals aged 18–65 years, ten normal weight (NW) (Body Mass Index (BMI): 18.5–24.99 kg/m2) and 10 obese (Ob) (BMI: 24.99–35.00 kg/m2) participated in this study, voluntarily. Moderate aerobic exercise (AE) (main circuit 30 min, between 40 and 59% of Heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Previous studies have reported either no relationship (Okuno et al., 2011 ) or a negative correlation (Lommatzsch et al., 2005 ) between plasma BDNF and BMI. Some studies suggest lower serum BDNF levels in obesity compared to normal‐weight individuals (Ceylan et al., 2023 ), indicating a potential risk for obesity in individuals with lower BDNF levels (Li et al., 2016 ). However, other studies have found no significant differences in basal BDNF levels between obese and normal‐weight individuals (Sandrini et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported either no relationship (Okuno et al., 2011 ) or a negative correlation (Lommatzsch et al., 2005 ) between plasma BDNF and BMI. Some studies suggest lower serum BDNF levels in obesity compared to normal‐weight individuals (Ceylan et al., 2023 ), indicating a potential risk for obesity in individuals with lower BDNF levels (Li et al., 2016 ). However, other studies have found no significant differences in basal BDNF levels between obese and normal‐weight individuals (Sandrini et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%